2018
DOI: 10.1155/2018/9395804
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antisenescence Effects of Bergamot Juice

Abstract: Aging is one of the main risk factor for the onset of cardiovascular diseases; one of the possible explanations could be linked to the age-associated overproduction of free radicals. This increase of oxidative stress can be overcome with a high intake of food antioxidants. In this context, a number of studies have been addressed to assess the antiaging potential of natural antioxidant compounds. Recently, it has been shown that the juice of bergamot (Citrus bergamia Risso et Poiteau), a fruit mostly produced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
58
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 51 publications
6
58
2
2
Order By: Relevance
“…Flavonoids also present numerous healthy effects. One of these is the antioxidant activity that prevents the risk of developing age‐related vascular disease …”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids also present numerous healthy effects. One of these is the antioxidant activity that prevents the risk of developing age‐related vascular disease …”
Section: Resultsmentioning
confidence: 99%
“…Citrus flavanone naringenin was shown to prevent myocardial cells from senescence through the modulation of cell cycle regulators, ROS levels, and mitochondrial metabolic activities [15]. The juice of bergamot (Citrus bergamia Risso et Poiteau) counteracted the senescence processes in senescent H9c2 cells and old mice [16]. All findings revealed that orange phytochemicals might have anti-aging effect on lifespan.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, we recently observed that NAR also exerts antisenescence effects. In particular, in H9c2 cardiomyoblasts submitted to oxidative stress by H 2 O 2 treatment, NAR contained the βgalactosidase activity, as well as the expression of p21 and p16, well-known markers of ageing [15]; furthermore, bergamot juice, containing a high amount of NAR, increased the genic expression of the antiageing markers SIRT1, Nrf2, and FOXO1 in cardiac tissues [16]. Noteworthly, NAR exhibits close structural analogies with well-known SIRT1 activators, such as such as resveratrol (RES) and quercetin [17][18][19][20].…”
Section: Introductionmentioning
confidence: 96%